2022
DOI: 10.1007/s11356-022-19583-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally relevant concentration of caffeine—effect on activity and circadian rhythm in wild perch

Abstract: We studied the ecological consequences of widespread caffeine contamination by conducting an experiment focused on changes in the behavioral traits of wild perch (Perca fluviatilis) after waterborne exposure to 10 μg L−1 of caffeine. We monitored fish swimming performance during both light and dark conditions to study the effect of caffeine on fish activity and circadian rhythm, using a novel three-dimensional tracking system that enabled positioning even in complete darkness. All individuals underwent three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
3
4
0
Order By: Relevance
“…Consistent with our results on general activity, exposure of wild perch ( Perca fluviatilis ) to 10,000 ng/L of caffeine (i.e. a nominal concentration identical to the high‐caffeine treatment in this study) did not affect their general activity during the day nor circadian activity (Cerveny et al, 2022). Similarly, exposure of larval zebrafish ( Danio rerio ) to 1 μg/L caffeine did not impact swimming speed (Zhou et al, 2019), and exposure between a range of 1 and 4070 μg/L did not affect total distance travelled compared to controls (Steele et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our results on general activity, exposure of wild perch ( Perca fluviatilis ) to 10,000 ng/L of caffeine (i.e. a nominal concentration identical to the high‐caffeine treatment in this study) did not affect their general activity during the day nor circadian activity (Cerveny et al, 2022). Similarly, exposure of larval zebrafish ( Danio rerio ) to 1 μg/L caffeine did not impact swimming speed (Zhou et al, 2019), and exposure between a range of 1 and 4070 μg/L did not affect total distance travelled compared to controls (Steele et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results on general activity, exposure of wild perch (Perca fluviatilis) to 10,000 ng/L of caffeine (i.e. a nominal concentration identical to the high-caffeine treatment in this study) did not affect their general activity during the day nor circadian activity (Cerveny et al, 2022). Similarly, exposure of larval zebrafish (Danio rerio)…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the highest caffeine concentration in Europe was found in the Aegean Sea, measuring 3.1 μg L À1 . Similarly, Cerveny et al (2022) provided data indicating frequent caffeine concentrations below 1 μg L À1 in aquatic environments, with a maximum of 39.8 μg L À1 in Europe and up to 1.0 mg L À1 in Costa Rica. In some of the most heavily polluted river sites, caffeine concentrations reached 6 μg L À1 (Bottoni et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…CAF is a psychoactive drug that belongs to the methylxanthines class and can cause several pharmacological (e.g., stimulant and diuretic) and biological (e.g., cell death and oxidative stress) effects in target and non-target species [ 8 ]. CAF is a non-selective antagonist of adenosine receptors [ 23 ], stimulating the central nervous system and affecting the activity of neurotransmitters [ 29 , 30 ]. Furthermore, several studies already showed acute toxicity of CAF to bacteria ( Pseudomonas putida, EC 50 (17 h) = 3490 mg/L), algae ( Scenedesmus subspicatus, EC 50 (72 h) > 100 mg/L), freshwater invertebrates ( Daphnia magna, EC 50 (48 h) = 182 mg/L), and fish ( Leuciscus idus, LC 50 (96 h) = 87 mg/L) [ 31 ], however, these studies report toxicity at concentrations well above those found in the environment ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%